2015
DOI: 10.1039/c5nr01297j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tuning of conductance and thermopower in helicene molecular junctions

Abstract: Helicenes are inherently chiral polyaromatic molecules composed of all-ortho fused benzene rings possessing a spring-like structure. Here, using a combination of density functional theory and tight-binding calculations, it is demonstrated that controlling the length of the helicene molecule by mechanically stretching or compressing the molecular junction can dramatically change the electronic properties of the helicene, leading to a tunable switching behavior of the conductance and thermopower of the junction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 112 publications
(197 reference statements)
5
84
0
Order By: Relevance
“…Moreover, [n]-helicene ligands are helically-shaped, so they possess a chirality despite the absence of enantiocenter. Due to these intrinsic properties, this family of ligands is widely employed for various applications, ranging from organic molecular electronics [33], probes for detection of chirality and sensing devices [34] to molecular junction [35].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, [n]-helicene ligands are helically-shaped, so they possess a chirality despite the absence of enantiocenter. Due to these intrinsic properties, this family of ligands is widely employed for various applications, ranging from organic molecular electronics [33], probes for detection of chirality and sensing devices [34] to molecular junction [35].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 6(b) we present the recalculated ZT value versus n using a typical value of phonon thermal conductance j ph ¼ 20pW K À1 [33][34][35][36][37] of similar molecules. It has been shown [32] that in some cases the phonon thermal conductance is inversely proportional to the square of molecule length L, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In some molecules when weak coupling and strong coupling interaction are coexisted, mechanically control could be able to achieve more obvious adjustment of thermoelectric properties. Theoretical studies for a helicene molecular showed that the conductance increased with increasing compressive strain and decreased with increasing tensile strain, whereas the opposite trend was observed for the Seebeck coefficient . The numerical result shown the sign of the Seebeck coefficient can be reversed when the tension and compression states are switched, indicating another way to realize the transition from n‐type to p‐type materials.…”
Section: Optimization Strategies For Ote Devicesmentioning
confidence: 91%